Relationships between metamorphism and deformation in the Nordmannvik nappe, south of Lyngseidet: a focus on high grade relics - Hibelot, Thomas (Universitetet i Tromsø, 2013)
The Nordmannvik nappe (Lyngen fjord, northern Norway) is a high grade tectonic unit dominated by mylonitic garnet-kyanite-mica gneisses, with additional calc-sillicates, mafics and high grade relics. The unit was principaly deformed during the Scandian event of the Caledonian orogeny, reaching at least an upper amphibolite facies. A metamorphic peak, set at a minimum of 750°C / 0.9 GPa, has been recorded in both metapelites and mafic bodies. Petrographic evidences have shown that Scandian garnet-kyanite-mica gneisses evolved by dehydratation reactions before their subsequent decompression in a late stage, coevally with the implementation of a mylonitic fabric. A main aspect of this work concerned the identification of high grade lenses in which the Scandian mylonitic fabric was not observed. Some of these lenses composed of weakly deformed garnet-sillimanite gneisses have reached a granulite facies identified by the assemblage Qtz + Kfs + Grt + Sil + melt. Such high grade rocks with some mafic lenses have shown evidences for a pre-Scandian metamorphic event most likely composed of a prograde orogenic path followed by a subsequent decompression of the high grade assemblages. Because pre-Scandian pelitic rocks are observed in the area, it is concluded that the Nordmannvik nappe must not be included in the oceanic rocks composing the Upper Allochton, as it is usually presented in the literature. Instead, petrographic similarities between rocks from the Nordmannvik nappe and from the lower units suggest that the Nordmannvik nappe belongs to the upper Middle Allochton, made of metasediments from the outermost Baltica margins. In addition and based on petrographic and structural elements, the phyllite unit which outcrops along the upper contact of the Nordmannvik nappe is suggested to have derived from the garnet-kyanite-mica gneisses rather than from the overlying mafics of the Lyngen Nappe Complex. Eventually, structural features support the Scandian character of the Nordmannvik nappe. Westward dipping foliation ...